2015
DOI: 10.1259/dmfr.20140302
|View full text |Cite
|
Sign up to set email alerts
|

The role of time-resolved imaging of contrast kinetics (TRICKS) magnetic resonance angiography (MRA) in the evaluation of head–neck vascular anomalies: a preliminary experience

Abstract: TRICKS sequences add important diagnostic information in cases of HNVAs, helpful for therapeutic decisions and post-treatment follow up. We recommend TRICKS-MRA use (if technically possible) as part of routine MRI protocol for HNVAs, representing a possible alternative imaging tool to conventional DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…There is no current literature comparing efficacy of contrast-enhanced CT to CTA or MRI and MRA for the evaluation of a pulsatile neck mass. Arterial phase, time-resolved (4-D) MRI may be useful for evaluation of possible paragangliomas in the head and neck [59][60][61], but it is not an initial imaging study of a new palpable neck mass.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…There is no current literature comparing efficacy of contrast-enhanced CT to CTA or MRI and MRA for the evaluation of a pulsatile neck mass. Arterial phase, time-resolved (4-D) MRI may be useful for evaluation of possible paragangliomas in the head and neck [59][60][61], but it is not an initial imaging study of a new palpable neck mass.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…Previous investigations described a good interobserver agreement when comparing TRICKS to DSA, although there is no evidence that TRICKS can replace DSA. 11 Some studies focused their attention on arteriovenous malformations (AVMs), 1214 suggesting good results studying dural AVM or AVF, although the authors reported low spatial resolution and vessel superposition. Concerning spinal vascular malformations, Saindane et al.…”
Section: Discussionmentioning
confidence: 99%
“…As such, TRICKS is particularly useful for diagnosing disease entities with aberrant flow between arterial and venous networks, including arteriovenous malformations, cranial and cervical DAVFs, and symptomatic cranial venous drainage patterns as well as excellent visualization of the course and contour of the cervical arteries and veins. Although still limited in temporal and spatial resolution compared to digital subtraction angiography (DSA), TRICKS serves as a noninvasive analogue to DSA without the risks of ionizing radiation 48 or invasive procedural risks 49 …”
Section: Time‐resolved Imaging Of Contrast Kineticsmentioning
confidence: 99%